Microbiology of the Gut of the Kola Nut Weevil, Balanogastris kolae - Femi-Ola, T. O. (University of Wisconsin Library, 2012)

(untitled)
Reports have shown that many insects have microbes in their gut system. Gut microbes are very important for insect vitality and much of their nutrition is derived from products of microbial metabolism. The habitat of Balanogastris kolae (Desbrocher des Loges) (Coleoptera: Curculionidae) suggests that they possess the ability to digest varieties of sugars particularly starch and protein materials present in the kola nut, Cola nitida Schott & Endlicher (Malvales: Malvaceae). The aim of this study was to characterize the gut bacterial communities of the kola weevil, B. kolae. To ascertain this, the gut bacterial community of a kola nut-feeding weevil, B. kolae was characterized using culture-dependent methods. The bacterial counts in the foregut, midgut and hindgut were 7.14 ± 0.11 × 10(6)cfu ml(-1), 2.68 ± 0.13 × 10(7) cfu ml(-1) and 1.43 ± 0.20 × 10(6) cfu ml(-1) respectively. There were no significant differences in the total bacterial count of the foregut, midgut and hindgut. The bacterial species were identified to be Fusobacterium nucleatum, Staphylococcus aureus, Bacillus subtilis, Corynebacterium fascians, Arthrobacter globiformis, Serratia marcescens, Bacillus brevis, Vibrio haemolyticus and Flavobacterium breve. The majority of these isolates were demonstrated to have both proteolytic and amylolytic activities.